KEMAMPUAN INPLEMENTASI MENAJEMEN PEMERINTAHAN, SIKAP KERJA, MOTIVASI KERJA DAN EFEKTIFITAS KERJA. - Slamet Riyadi ' (JIANA ( Jurnal Ilmu Administrasi Negara ), 2014)
The Ability Governance Implementation Management, Work Attitude,Work Motivation and Work Effectiveness. This study aims to determine the effect of theimplementation of government management ability, work attitude and motivation to workon the effectiveness of the headman, either partially or jointly. This research uses descriptivequantitative method with correlation and regression statistical analysis. The study populationwas urban village located in Depok were 63 wards. Samples were taken 15 villages with arandom sampling technique. Techniques of data collection using a questionnaire based on theperception of the respondents according to a Likert scale. Data analysis was performed in twoways: descriptive analysis and inferential analysis. The results showed that the ability of theimplementation of government management, work attitude and work motivation headman, eitherpartially or jointly have influence on the effectiveness of the headman significant and positive.The dominant influence on the effectiveness of the headman is variable work motivation. But theoverall effect of the implementation of the ability of government management, work attitudes,work motivation on the effectiveness of 0.707 and in other words the effectiveness of workcontribution headman only 49.9%. The remaining 50.1% is determined by other factors suchas employee loyalty, personality and expertise, and for the further research needs to be done inconnection with the performance of employees.Keywords: government management implementation ability, work attitude, work effectiveness.